2016
DOI: 10.1155/2016/4986034
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Olfactory Function in Postviral Olfactory Dysfunction Patients after Acupuncture Treatment

Abstract: Introduction. The aims of this study were to assess the impact of traditional Chinese acupuncture (TCA) in postviral olfactory dysfunction (PVOD) patients who were refractory to standardized treatment and to compare the results with the impact observed in an observation group. Methods. Fifty patients who presented to the outpatient clinic with PVOD and were refractory to standardized treatment were included: 25 were treated with TCA and 25 patients were simply observed. A subjective olfactory test was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 16 publications
2
56
0
1
Order By: Relevance
“…29,30 Such cumulative insult, together with the fact that the challenge of regeneration in advanced age is significantly reduced, might be the reason why the recovery of olfactory functions after postinfectious olfactory loss decreases with increasing age. When it comes to the sex of the participants, in line with other studies 6,10,15,20 , this predictor was not significantly associated with the outcome. Intriguingly, the interval between the first and the second assessment 6,15,20 and the duration of disease until the first baseline test did not play a significant role in the model.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…29,30 Such cumulative insult, together with the fact that the challenge of regeneration in advanced age is significantly reduced, might be the reason why the recovery of olfactory functions after postinfectious olfactory loss decreases with increasing age. When it comes to the sex of the participants, in line with other studies 6,10,15,20 , this predictor was not significantly associated with the outcome. Intriguingly, the interval between the first and the second assessment 6,15,20 and the duration of disease until the first baseline test did not play a significant role in the model.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the role played by the disease duration, studies in literature are contradictive. Some results show that a longer disease duration is associated with less subsequent improvement, 2,6,14,15,20 although others 10,21 observed that longer periods after onset of olfactory loss were positively related to recovery. At odds with previous work, disease duration was unrelated to outcome, although the b value was negative, suggesting that the longer the disease, the lower the olfactory recovery (Table I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Dai et al produced similar results, with 11/25 patients in the TCA group having improved olfactory function compared to 4/25 in the no treatment group (p = 0.031). 56 Frequency of TCA treatment differed between these 2 studies, and neither paper reported any adverse events related to TCA. Summary:…”
Section: Acupuncturementioning
confidence: 96%
“…Traditional Chinese acupuncture (TCA) was evaluated as a treatment for PVOD in 2 level 4 studies after failure to respond to 1 to 6 months of oral steroids, vitamin B, olfactory training, or topical steroids (Table 10). 56,57 Vent et al demonstrated an increase in mean TDI score from 13.5 to 17.9 after TCA. 57 Additionally, 8/15 patients attained an increase in TDI score of ࣙ6 points (MCID), significantly improved compared to controls receiving vitamin B complex (p = 0.02).…”
Section: Acupuncturementioning
confidence: 99%